Migration and education: A narrative approach to the experience of foreign students in Portugal (UCL Press, 2018)
Non-English-speaking countries are attracting burgeoning numbers of foreign students, yet research regarding these students' experiences remains rather scarce. In line with global tendencies, Portuguese universities are seeing substantial growth in foreign student enrolment. This paper addresses the lived experiences of foreign students in the period following their arrival in a new cultural context, discussing the role that language and social support play in their adaptation. Rooted in a narrative approach, this paper is based on 41 indepth biographic interviews. The findings indicate that the ways in which students deal with the challenges of living and studying in a foreign country are highly diverse. Nevertheless, a universal aspect of their narratives is the central role assumed by social support. Although social support has beneficial outcomes for foreign students' adaptation, if provided inadequately it can lead to less positive outcomes and even to marginalization.